Issues on the resettlement of Pasar Besar Siti Hajar, Kelantan / Nur Farhan Muniri Abdullah and Mohd Fisal Ishak - Abdullah, Nur Farhan Muniri; Ishak, Mohd Fisal (2019)
The purpose of this study is to identify the challenges faced by market vendors on their resettlement. The objective of this research is to identify the facilities provided at Pasar Besar Siti Hajar, Pasir Puteh, Kelantan on the resettlement facilities provided to them. This study also focuses on the challenges faced by market vendors regarding the facilities provided at Pasar Besar Siti Hajar. In order to achieve the aim of this study, questionnaires were randomly distributed to the market vendors and observation of the area was conducted. Findings from this study revealed that the market vendors faced challenges such as high cost of rental, cost of mobilization, size of market and the location of the new settlement. This study sheds some light on why some vendors choose not to move to the Pasar Besar even though they were instructed by the local authority to do so.